TRANSFORMING WORKFORCE DYNAMICS: THE ROLE OF ARTIFICIAL INTELLIGENCE IN SHAPING HR PRACTICES - Razak, Ikhsan S. Abd (Management Studies and Business Journal (PRODUCTIVITY), 2025)
The integration of artificial intelligence (AI) in human resource (HR) practices has become increasingly critical in the era of Industry 4.0. However, many organizations encounter significant challenges in adopting this technology effectively. This study aims to explore the future opportunities AI offers to reshape HR strategies and workforce dynamics while identifying the challenges associated with its implementation. Utilizing a Systematic Literature Review (SLR) approach based on the PRISMA protocol, data were collected from various academic databases to analyze relevant studies on AI applications in HR. The findings reveal that AI enhances talent acquisition, personalized employee development, and optimizes workforce analytics, while also supporting more inclusive and equitable HR policies. This study provides practical insights for organizations to adopt AI ethically and strategically, emphasizing the importance of developing supportive policies to facilitate effective integration. These results contribute to advancing both academic research and practical applications in the intersection of AI and HR management.